PENGARUH KEANDALAN AKRUAL, TINGKAT UTANG DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIAPERIODE 2016-2020 - Maria Immaculata Bahantwelu; Piter Arson Welay (Jurnal Ilmiah Akuntansi, 2025)
The share price is the price of a share that occurs on the stock market at a certain time which is determined by market players and determined by supply and demand. Companies are required to have good performance so that investors are interested in investing because the company's performance is reflected in the share price. There are several factors that influence share prices, including: Accrual Reliability, Debt Level and Net Profit Margin.This research aims to determine the effect of accrual reliability, debt levels and net profit margin on share prices in manufacturing companies in the basic industrial and chemical sectors listed on the Indonesian Stock Exchange for the 2016-2020 period. The research method used is quantitative, the research population is 79 companies and the sample is 20 companies using purposive sampling. Financial data was obtained from www.idx.co.id and analyzed using the SPSS version 22 program.Based on the research results, it can be concluded that: 1) accrual reliability has a positive effect on stock prices. 2) debt levels have a negative effect on stock prices. 3) net profit margin has a positive effect on stock prices. 4) accrual reliability, debt levels and net profit margin simultaneously influence stock prices.